2022
DOI: 10.3389/fvets.2022.882423
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gut Microbiota Between Healthy and Diarrheic Horses

Abstract: Increasing evidence reveals the importance of gut microbiota in animals for regulating intestinal homeostasis, metabolism, and host health. The gut microbial community has been reported to be closely related to many diseases, but information regarding diarrheic influence on gut microbiota in horses remains scarce. This study investigated and compared gut microbial changes in horses during diarrhea. The results showed that the alpha diversity of gut microbiota in diarrheic horses decreased observably, accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Previous studies showed that diarrhea was mainly linked to intestinal dysbacteriosis [ 6 , 13 ]. It was also revealed in previous studies that gut microbiota imbalances occur in diarrheic yaks on the plateau [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies showed that diarrhea was mainly linked to intestinal dysbacteriosis [ 6 , 13 ]. It was also revealed in previous studies that gut microbiota imbalances occur in diarrheic yaks on the plateau [ [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 66%
“…Finally, we explored the marker bacteria between yaks in groups C and S, and we found 8 phyla and 54 genera were significantly different between two groups. Among those genus, lower abundance of Lachnospiraceae _AC2044_group and p_251_o5 was reported in diarrheal horses [ 48 ], Elusimicrobium in Type 2 diabetes [ 49 ], Methanobrevibacter in cirrhotic patients [ 50 ], [Eubacterium]_xylanophilum_group in intestinal injury mice induced by radiation [ 51 ], Candidatus_Saccharimonas in colitis mice [ 52 ], Atopobium in Chlamydia trachomatis infected women with infertility [ 53 ], and [Eubacterium]_siraeum_group in neurobehavioral injury mice induced by lead [ 15 ]. The higher abundance of these genera in group S may contribute to a decrease in diarrhea in yaks.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include infectious agents such as bacteria, viruses, parasites, and protozoa ( 34–36 ), diseases like inflammatory bowel disease and colitis ( 37 , 38 ), as well as other factors such as dietary changes, stress, and antimicrobial therapy ( 30 , 39 ). However, among these various factors, dysbiosis of the gastrointestinal microbiota emerges as a crucial underlying mechanism driving the onset of diarrhea ( 40 ). Therefore, restoring disbalanced gut microbial community may be an effective approach for treating diarrhea in horses.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work based on a population of 55 colitic horses and 36 healthy controls observed similar reductions in the dominant Bacillota families Ruminococcaceae and Lachnospiraceae (including Faecalibacterium ) in horses with colitis [ 70 ]. Horses with diarrhea showed similar changes at the phylum level and significantly reduced RA values of several SCFA-producing genera, including Weissella [ 71 ], suggesting that these dysbiotic changes can occur independent of inflammation. SCFAs are essential carbon sources for colonocytes [ 11 ], and butyrate in particular regulates cellular proliferation and immune responses via histone deacetylase (HDAC) inhibition [ 10 ] and tight junction permeability [ 13 ].…”
Section: Discussionmentioning
confidence: 99%